Sediment analyses (pH, electrical conductivity, mag. susceptibility, loss on ignition, remission and pXRF) and radiocarbon ages from the Araplı catchment in the Pergamon Micro-Region, western Turkey - Joris Starke; Brigitta Schütt; Moritz Nykamp; Robert Busch; M Doğan; Fabian Becker (PANGAEA, 2025)
The dataset was collected from seven sediment cores along a transect spanning the Araplı alluvial fan, east of ancient Pergamon, in the eastern lower Bakırçay plain, Pergamon micro-region, Türkiye. The cores were taken, described, sampled, and analyzed in the field and at the Bergama excavation house in October 2023. The soil description was conducted after Schoeneberger et al. (2002). Sediment samples were taken at irregular intervals and orientated along layer boundaries; samples include 3 cm of sediment in fine earth and 5 cm in gravelly material. Reported sample depths are simplified and given by their mean depth. Samples (n = 293) were analyzed for pH value, electrical conductivity, gravel content (sieve separate < 2 mm and > 2 mm), remission (sediment color using a spectrophotometer), loss on ignition (LOI, at 550 °C and 900 °C) after Dean (1974), mass-specific magnetic susceptibility (calculated according to Dearing, 1994), and element composition (portable energy-dispersive X-ray fluorescence). Results of radiocarbon dating of samples taken from the cores are included.